PELATIHAN PEMASANGAN POMPA HIDRAM DALAM RANGKA MENGATASI KEKURANGAN AIR BERSIH DI WILAYAH SUMBA TIMUR - Dwi Joko Siswanto; Agustin Nurahndayanti (JURNAL NAGARA BHAKTI, 2022)
This community service activity is motivated by the lack of clean water in the East Sumba district, NTT Province. The need for clean water is one of the basic needs that must be met, it will have an impact on the level of public health if their needs are not fulfilled. There are problems including: (a) the stunting rate of the East Simba community is quite high, which is around 30% of the number of population; (b) the level of public health that is susceptible to disease; (c) community immunity is low. The purpose of this activity is to discuss efforts to overcome the difficulty of clean water which has been the main problem in East Sumba. This service uses a training approach to hydram pump installation, while the target of implementation is the community around East Sumba district who are in areas where clean water is difficult. The results of the implementation of this service are as follows: (1) overcoming a number of 5,040 people who have had problems with clean water; (2) the decline in stunting rates to 29%; (3) water can also be used for farming with a drip pattern for vegetable crops.